Defect Rich Hierarchical Porous Carbon for High Power Supercapacitors - Cai, Peng; Zou, Kangyu; Deng, Xinglan; Wang, Baowei; Zou, Guoqiang; Hou, Hongshuai; Ji, Xiaobo (Frontiers in Chemistry, 2020)
Tuning hierarchical pore structure of carbon materials is an effective way to achieve high energy density under high power density of carbon-based supercapacitors. However, at present, most of methods for regulating pores of carbon materials are too complicated to be achieved. In this work, a durian shell derived porous carbon (DSPC) with abundant porous is prepared through chemical activation as a defect strategy. Hierarchical porous structure can largely enhance the transfer rate of electron/ion. Furthermore, DSPC with multiple porous structure exhibits excellent properties when utilized as electrode materials for electric double layer capacitors (EDLCs), delivering a specific capacitance of 321 F g-1 at 0.5 A g-1 in aqueous electrolyte. Remarkably, a high energy density of 27.7 Wh kg−1 is obtained at 675 W kg−1 in an organic two-electrode device. And large capacity can be remained even at high charge/discharge rate. Significantly, hierarchical porous structure allows efficient ion diffusion and charge transfer, resulting in a prominent cycling stability. This work is looking forward to providing a promising strategy to prepare hierarchical porous carbon-based materials for supercapacitors with ultrafast electron/io¬¬¬n transport.